Integrating Sufism and Environmental Ethics: A Comparative Study of al-Qushayrī and Holmes Rolston III - Afda Alif Muhammad; Muhammad Ihza Fazrian -; Waryani Fajar Riyanto (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
The global environmental crisis intensifying in our era highlights the need for new conceptual approaches to address this existential issue. This study examines the relationship between environmental ethics and Sufism, based on systemic values inherent in Holmes Roston III and the Sufistic concept of self-purification. This qualitative research employs document analysis, focusing on al-Qushayrī's Subtle Allusions and Holmes Rolston III's Environmental Ethics, analyzed through a comparative framework and supported by secondary data. The study investigates the Sufistic concepts of ascetism, fear of God, and contentment alongside the systemic values of environmental ethics. It proposes the integrative concepts of prevent-repair, care-guard, and conviction-kindness as key outcomes. These findings underscore the importance of environmental ethics, personal spirituality, and intrinsic awareness, providing both theoretical and practical insights. Contribution: Theoretically, this study advances the integration of Sufism and environmental ethics through combining Sufistic values (internal) with systemic values (external). It provides a framework for cultivating a balanced attitude and a conscious relationship with God, humans, and nature, grounded in Qur’anic principles and ecological awareness.